Pengaruh Kepemilikan Institusional, Price To Book Value Dan Ukuran Perusahaan Terhadap Return Saham Pada Perusahaan Manufaktur Sektor Food And Beverages Yang Terdaftar Di Bei. - Cut Fitrika Syawalina (Jurnal Akuntansi Muhammadiyah (JAM), 2014)
This research is aimed to investigate the effects of institutional ownership,price to book value, and firm size on stock return at the Indonesia Stock Exchange. The population examined in this research is food and beverages companies listed in the Indonesia Stock Exchange for three-years periods (2008-2010). This research uses a cencus method. After selected, there were 39 companies as target population. Meanwhile, the analytical method that is applied in this research is multiple regression analysis. In short, the findings of this research indicated that both simultaneously and partially, institutional ownership, price to book value, and firm size influence the stock return of food and beverages companies listed in the Indonesia Stock Exchange.